Regression analysis of the symptoms - Gruden-Pokupec, Josipa-Sanja; Gruden, Vladimir, ml.; Orihovac, Željko (2009)
Abstract: Stomatopyrosis of 'burning mouth' syndrome, in a narrower sense of definition, is a condition characterized by sensation of burning and heating in mouth, despite its normal mucosa. This research has been directed towards treatment of stomatopyrosis, putting emphasis on the implementation of psychopharmacotherapy and psychotherapy. The research was conducted on altogether 120 respondents suffering from stomatopyrosis. The respondents were divided into two equal groups: each one comprising 60 members. All the respondents were treated by means of a standard topical therapy. All the patients were assessed clinically and by means of psychological tests measuring depression and anxiety four times: once before the treatment, after one month, after two months and after four months since the beginning of the treatment. The acquired data were afterwards statistically processed. Our research led to the conclusion that stomatopyrosis occurs with elderly people, primarily women.
Regarding their occupation, majority of the respondents were clerks, followed by retirees. The burning sensation in mouth was present with all the respondents, the dominating site being the lips, while the nature of sensation was reported as mostly unbearable. Anxiety, tension and stress tend to aggravate the symptoms. When grading the symptoms on VAS, i.e. visual analogous scale, the subjective assessment of symptoms was marked as 7–8 cm, which shows a high degree of burning sensation. According to our study, the quantity of saliva, which was at the beginning of the research slightly decreased, normalized after the treatment. Apart from the clinical investigation of stomatopyrosis, we applied Depression and Anxiety questionnaires. During the therapy, the results of the depression test have shown a decrease in depression (from 56.7% to 0.00%), which is particularly apparent in the group treated by autogenic training and in the first group of respos, i.e.
the one treated with antidepressants. The Anxiety tests have shown a higher percentage and intensity of anxiety with men (62.5%, as opposed to women – 32.5%) in the beginning, which has dropped to 7.5% with men during the treatment and 8.8% with women. Clinical presentation of stomatopyrosis has also apparently improved. This improvement in clinical symptoms and psychological condition of patients is statistically significant. On the basis of our research, we have concluded the following: the comorbidity of stomatopyrosis with the phenomena of anxiety and depression proves that, among other factors, there is a psychogenic aetiology of this disease. Further research should provide answers to the questions whether stomatopyrosis is a psychosomatic or a conversive disorder. Antidepressants and anxiolytics have an important role in the therapy of stomatopyrosis.
Autogenic training, which is a psychotherapeutic anxiolytic technique, is a therapy of choice for stomatopyrosis, which contributes not only to the elimination of oral complaints, but to the emotional rehabilitation of the patients as well
Bibliografija: 36 jed
Sažetak
Keywords: Stomatopiroza -- Sindrom pekućih usta -- Depresija -- Anksioznost -- Autogeni trening